SUPPORTING THE RURAL ENVIRONMENT IN ROMANIA THROUGH FINANCING FROM EUROPEAN FUNDS IN THE TRANSITION PERIOD 2021-2022 - Nicoleta ILIE (MARIN); Iulia Alexandra OPREA; Eliza GHEORGHE; Alecsandra PĂRNUȘ (RUSU) (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The continuation of financial assistance for Romanian farmers and entrepreneurs from rural areas during the years 2021–2022, which will serve as the CAP's transitional years, has been regulated at the EU level. From the standpoint of financing the rural area in Romania, the current article intends to highlight the contribution of the National Rural Development Program's initiatives throughout this period. The measures that could be accessed during the transition period are synthetically presented. The support granted to the Romanian agricultural and non-agricultural sector will increase the degree of modernization of farms, their expansion and development, will support the installation of young farmers who start an agricultural activity for the first time as holding managers and the development of farms led by young people who were installed during previously, diversifying the valorization of agricultural production as well as supporting the implementation of actions within local development strategies. The National Programme of Rural Development (NRDP) budget for the transition period 2021-2022 was approximately 3.26 billion euro, and the funds must be spent by December 31, 2025 at the latest.